(untitled) (ModaPalavra e-periódico, 2009)
The research approaches the necessary knowledge for the professional formation of the modelist of clothes, as well as of the productive sectors which its work is tied. A search to characterize its basic functions and necessary abilities for the quality of the modeling. In this direction, the research considers to identify the formation of the modelists that work in the companies of clothes in Santa Catarina, as well as the use of system CAD as work tool. The methodologists procedures consolidate in the proposal of the quantitative method, with exploratory and descriptive boarding, to be carried through a field research. It is intended with the gotten data to present pointers that will help in the elaboration of actions that allow to contribute for the complementation of the formation of the modelist, and the valuation of its work on the part of the companies of clothes.